Reef fish community structure and live coral cover in selected reef flats of Taklong Island National Marine Reserve, Guimaras, Philippines - Gomez, Zemrec G.
Evaluation and monitoring of Marine Protected Areas are important in assessing its reef status in order to improve management and protection on the area. Community structure of fishes in selected reef flats of Taklong Island National Marine Reserve (TINMR), Nueva Valencia, Guimaras were investigated in December 2015. Using underwater fish visual census (UVC), data on fish diversity, density and biomass were estimated. Percent liver coral cover was determined through line intercept method. There were 59 species in 22 families of fishes recorded in 4 reef flats namely, Banago, Talisay, Kalirohan and Calaparan with biomass (in MT km-2) ranging from 7.5 (Talisay) to 44.2 (Calaparan). Fish density (in individuals 1000m-2) ranged from 252 (Talisay) to 796 (Calaparan) individuals 1000m-2. Live coral cover ranged from fair (28%, Kalirohan) to excellent (78%, Calaparan). Indicator and target species comprised as much 96% of total counts and 98% in total fish biomass. The family Pomacentridae was the most dominant. Nearly all species seen in TINMR were herbivores and invertebrate feeders but other feeding guilds were also represented. Linear regression analyses showed weak relationship between live coral cover and fish community structure (p>0.05). Calaparan had the best fish community structure with excellent reef among 4 sites. But Talisay showed poor fish structure despite having good coral cover. So, there must be other factors influencing fish structure other than live coral cover that needs elucidation. Applying the current standard used to evaluate Marine Protected Areas based on reef fish community structure, TINMR can be described as very poor to poor in fish diversity, poor to moderate in fish density, and low to very high in fish biomass.